Sandwich Structure Based On Corrugated-Core: A Review - N. Z. M., Zaid; M. R. M., Rejab; N. A. N., Mohamed (EDP Sciences, 2016)
Sandwich structures are commonly based on polymeric foam and honeycomb core material, for use in lightweight applications such as fuselage in aero plane, hull in marine construction and others. A review of sandwich structure based on corrugated-core is proposed and presented in this paper. Firstly, this paper aims to provide a means of comparing available sandwich structure in industries. Secondly, this paper aims to provide sandwich structure with corrugated-core for future research development efforts in field of sandwich construction. This paper starts with introduction of composite material such as sandwich structure, the advantages of sandwich structure was shown. After that these papers provide the structure of sandwich structure which includes the two faces and the cores. Furthermore, sandwich structure with different cores, which is honeycomb, foam core and corrugated core are discussed. At the end, the paper discussed more on corrugated-core for future research development.